Engineered design and fabrication of long lifetime multifunctional devices based on electrically conductive diamond ultrananowire multifinger integrated cathodes. Issue 41 (4th October 2016) - Saravanan, Adhimoorthy; Huang, Bohr-Ran; Manoharan, Divinah; Kathiravan, Deepa; Lin, I.-Nan
Abstract : Multi-functional vacuum electron field emission ( V EFE ) devices were developed using a laterally arranged multi-finger configuration with negative biased ultrananocrystalline-diamond graphite (NBG -UNDG) cathode/anode materials. Abstract : Multi-functional vacuum electron field emission ( V EFE ) devices were developed using a laterally arranged multi-finger configuration with negative biased ultrananocrystalline-diamond graphite (NBG -UNDG) cathode/anode materials. The NBG -UNDG based multifinger lateral electron field emitter (ML-EFE) devices were fabricated using micropatterning and a simple lift-off process. The fabrication process of ML-EFE devices is observed to markedly enhance the electron field emission (EFE) properties of NBG -UNDG materials. The EFE investigations of ML-EFE devices revealed a low turn-on field for EFE at a voltage as low as 2.02 V μm −1 with a high current density of 1.51 mA at an electric field of 2.6 V μm −1 . The presence of multi-layer nanographite (ng) in NBG -UNDG diamond nanowires and a Au interlayer at the film-to-substrate interface are presumed to be the main factors, which result in superior EFE properties for NBG -UNDG ML-EFE devices. The enhanced properties of NBG -UNDG based multifinger integrated cathodes have noteworthy potential for the generation of new display panel applications. Using NBG -UNDG ML-EFE devices as cathodes, a microplasma device was fabricated that can generate plasma at a low voltage of 260 V. Also, a photodetector, which provides an excellent photoresponsivity of 1.7 A W −1, was demonstrated using NBG -UNDG ML-EFE devices as sensing materials. Moreover, a NBG -UNDG based self-aligned cathode and gate V EFE transistor was fabricated, which exhibits enhanced transistor characteristics with a low turn-on gate voltage of 320 V. The fabrication of these NBG -UNDG devices, which can be operated at high power and under various vacuum conditions with long lifetime, demonstrates a practical approach in diamond based vacuum microelectronics and integrated circuits.